Transmission of Texts and New Technologies: Memory or Transformation? - Pietrzak-Thébault, Joanna (Załącznik Kulturoznawczy, 2023)
The paper discusses some aspects of possibilities and dangers that new digital technologies bring in the camp of transmission of texts, especially the literary ones, and their scholar edition. While the new trends and achievements are still under discussion, a glance towards the similar situation of some 500 years ago, when printing press was introduced to replace, step by step, a manuscript communication, could be useful to understand what we experience and to foresee some ways these new technologies will probably undertake.